THE EFFECTIVENESS OF COOPERATIVE LEARNING TYPE OF NUMBER HEAD TOGETHER (NHT) TO MATHEMATICS LEARNING OF STUDENTS IN SMP MUHAMMADIYAH 2 MINGGIR - Fatimah Fatimah; Abdul Taram (Universitas Ahmad Dahlan, 2017)
Â This research was done because the results of students' mathematics learning is still relatively low. Students are reluctant to ask about the material they have not understood that the learning outcomes obtained less optimal. This research aims to determine the results of learning mathematics using of cooperative learning model type of NHT (Numbered Heads Together) toward mathematic learning of student grade VIII at SMP Muhammadiyah 2 Minggir Sleman Regency of Even Semester in Academic Year of 2015/2016. This was design is Posttest-Only Control Design. The population in this research were students class VIII SMP Muhammadiyah 2 Minggir Sleman Regency. Samples of this research using random sampling techniques derived from class VIII B as an experimental class and VIII C as the control class. The data collection is done with the test method. Testinginstrumentusing validity test and reliability test. Data were analyzed before using hypothesis testing with t-test first using analysis prerequisite test including normality test, and homogeneity test Based on calculations by the significant level Â and the degrees of freedom 49, we concluded that: (1) There are differences in learning outcomes ofÂ students learning math using cooperative learning model type of NHT with learning using conventional learning model. This is indicated by the results of the first test of the hypothesis that and , so that . (2) The type of cooperative learning model NHT more effective than the conventional learning model. It is shown on the second hypothesis that the test results and , so that .